Fuel ethanol production from starchy grain and other crops: An overview on feedstocks, affecting factors, and technical advances. (April 2022) - Li, Jun; Zhao, Renyong; Xu, Youjie; Wu, Xiaorong; Bean, Scott R.; Wang, Donghai
Abstract: The substitution of gasoline by ethanol with different ratios is commercialized around the world. In this review, an overview on feedstocks, affecting factors, and technical advances in starch ethanol production has been systematically presented. Most ethanol is produced from starchy crops, among which corn, wheat, and sorghum are the major contributors. Additional starchy crops have also been studied for ethanol production but have not yet been industrialized. Degerming and decortication can improve ethanol yield with value-added products produced for ethanol valorization. Starchy crops varieties with high waxy starch, low starch-lipid complex formed, and low protein cross-linking after cooking are more productive for ethanol production. Starch and fiber can not only be separated for first- and second-generation ethanol production, respectively, but also combined for 1.5-generation ethanol production, which is techno-economically feasible. Process integration could be great routes to improve competitive advantage of ethanol due to reduced production cost, but relevant techniques need further advances. Prehydrolysis of protein during mashing can increase FAN content thus improve ethanol yield, but its economics need to be assessed. Value-added protein extracted from DDGS for extensive applications can also valorize ethanol. Recommendations for further improving starch ethanol production and valorizing ethanol have also been included. Highlights: Starchy crops are the most contributor to fuel ethanol production. Starch-to-ethanol conversion is largely affected by inherent nature of starchy crops. Starch-to-ethanol conversion is also affected by processing patterns and conditions. 1.5-generation ethanol production is viable with oil production by germ preseparation. Protein rich products from DDGS generate additional profits to ethanol production.